IJABE Guidelines for Authors - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
Int. J. Agric. & Biol. Eng (IJABE) is an international peer-reviewed open-access journal sponsored and published jointly by US-based Association of Overseas Chinese Agricultural, Biological and Food Engineers (AOCABFE) and Chinese Society of Agricultural Engineering (CSAE). The ISSN 1934-6344 and eISSN 1934-6352 numbers for the IJABE have been registered, which allow IJABE to publish in both online and hard copy. Open access IJABE provides easy sharing of knowledge, and is thus in the best interest of authors, readers, and increases the availability, accessibility, visibility and impact of the papers, and journal as a whole. IJABE aims at facilitating development of agricultural and biological engineering, promoting the prosperity of academics, and improving international academic exchange and cooperation. This journal strives to publish the latest high-quality research from a diverse array of topics from the international community. Our readers are from the international scientific community as well as educators, policy makers, agricultural engineers and scientists, and interested members of the public around the world.